Figures 10A–F. Zygophylax sagamiensis, stn 63. A, colony. B in Deep-water hydroids (Hydrozoa: Leptolida) from Macquarie Island ... - Watson, Jeanette W. (Zenodo, 2003)
Figures 10A–F. Zygophylax sagamiensis, stn 63. A, colony. B, distal part of branch. C, hydrotheca with multiple marginal replications. D, pedicellate nematotheca on hydrorhiza. E, coppinia. F, hooded gonothecae from coppinia. Scale bar: A, 25 mm; B, 0.5 mm; C, 0.2 mm; D, 0.1 mm; E, F, 0.25 mm. ... : Published as part of Watson, Jeanette W., 2003, Deep-water hydroids (Hydrozoa: Leptolida) from Macquarie Island, pp. 151-180 in Memoirs of Museum Victoria 60 (2) on page 160, DOI: 10.24199/j.mmv.2003.60.18, http://zenodo.org/record/12207807 ...